Pretext not to Commence Criminal Charge Against Tax Crime - I. G. Ragozina (Сибирское юридическое обозрение, 2014)
The article deals with consequences of legislative restriction of the opportunity to undertake prosecution against tax crime due to the introduction of “defensive” pretext for this decision making.